2001
DOI: 10.1016/s0735-1097(01)01109-3
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the ontario acute myocardial infarction mortality prediction rules

Abstract: The Ontario AMI mortality prediction rules predict quite accurately 30-day and one-year mortality after an AMI in linked hospital discharge databases of AMI patients from Ontario, Manitoba and California. These models may also be useful to outcomes and quality measurement researchers in other jurisdictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
233
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(248 citation statements)
references
References 9 publications
8
233
0
2
Order By: Relevance
“…The derivation and validation of this model has been described elsewhere. 17 The regression models incorporated a variable denoting the number of years since 1992, which allowed us to determine changes in the use of each medical therapy over time. We modified each model by incorporating an interaction between time and each physician and hospital characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…The derivation and validation of this model has been described elsewhere. 17 The regression models incorporated a variable denoting the number of years since 1992, which allowed us to determine changes in the use of each medical therapy over time. We modified each model by incorporating an interaction between time and each physician and hospital characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic status was derived using ecological income measures (i.e., median neighborhood household income) from 1991 official Canadian census data. Measures of illness severity incorporated variables included in the Ontario AMI mortality prediction rule for 30-day and 1-year mortality (11,13). In addition to diabetes (with and without complications), clinical variables included the following: shock, congestive heart failure, pulmonary edema, cardiac arrhythmia, stroke, malignancy, acute renal failure, and chronic renal failure.…”
Section: Sources Of Datamentioning
confidence: 99%
“…In addition to diabetes (with and without complications), clinical variables included the following: shock, congestive heart failure, pulmonary edema, cardiac arrhythmia, stroke, malignancy, acute renal failure, and chronic renal failure. The clinical prediction rule has been validated against several population-based AMI cohorts illustrating good predictive accuracy (areas under the receiver operating curve of 0.77 in validation datasets) (13).…”
Section: Sources Of Datamentioning
confidence: 99%
“…This current algorithm was utilized to develop predictive models for mortality within the Ontario population and has been further validated with the new ICD-10 coding. 120,121 Accuracy of this diagnosis when compared to the hospital chart was approximately 94%. 122 Other studies validating CIHI diagnostic codes for MI demonstrated a sensitivity of 89% and positive predictive value of 89%.…”
Section: Myocardial Infarctionmentioning
confidence: 94%